Research universities: some basic specific features - Tuyen, Hoang Van; Minh Nga, Nguyen Thi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Research university is a model for the best practice to link teaching and research activities. The Research University increasingly attracts attention of scholars, researchers and science-education policy makers in many countries including also developed nations. The Research University has high specific features. It is costly to follow this model and the development of this model requires a developed institutional environment. Therefore, according to some researchers and scholars, it is a hard problem to develop the model of Research University in its right senses, especially for developing countries. This paper gives contributions to understand better some basic specific features of this model of universities. Code: 15060901